Analisis Pengaruh Belanja Modal Dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2015-2022 - Rhima Kusuma; Rivana Maharani; Septi Nur Sari; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the workforce, both male and female workers, showing an insignificant negative impact on economic growth in Indonesia, which shows a reduction in poverty with an increase in poverty of 1%. The relationship between capital expenditure, labor force, and economic growth is analyzed, with the labor force variable showing an insignificant effect on economic growth. The R2 value of 0.524712 indicates that capital expenditure and labor force can explain 52% of the variance in economic growth in Indonesia. Autocorrelation testing using the Durbin Watson test is used to detect correlation between variables over time. Excess labor in certain sectors is seen as an opportunity, not a problem, because it contributes to increasing output and supports other sectors.